(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The purpose of the article is to elucidate the essence of financial incentives for innovation and investment development of environmental entities in the region. The organizational and economic mechanism of using the innovative and investment potential of sustainable development, provides for planning, financial provision, state regulation and stimulation, control of the innovative and investment potential of sustainable development. Financial support for sustainable development is based on financial resources of foreign and domestic investors, as well as other sources (this can be both budget expenditures and innovation activities of strategically important sectors of the economy, as well as funds of business entities and households) The structure of financial security includes four forms, based on financing systems: self-financing – is to ensure the reproduction of production from the region’s own financial resources. The positive side of this form of financial support is to make the most efficient use of available resources by speeding up the terms of their circulation; lending is the main form of financial support for the socio-ecological and economic needs of the region through temporary use of borrowed resources. It is implemented on the principles of payability, repayment, time and material security of loans. Lending allows the use of the same financial resources to various business entities, accelerates their turnover and contributes to an increase in the efficiency of activities, and as a result – significant savings in social capital are achieved; budgetary allocations are state financing in the form of interbudgetary transfers; investment as a form of financial security is realized on the basis of investments – long-term investments in the economy, social and environmental spheres. The financial provision of policies to promote sustainable development in the region is a focused process involving attracting, distributing and reallocating funds to finance incentive measures to achieve the social, economic and environmental goals of the region, with the main objective being to achieve sustainable development in the region, with all the signs of sustainability. The main subjects of financial support for the policy of stimulating sustainable development of the region are: economic entities in the region, state and regional authorities and households.